Deixa a gira girar: como o racismo religioso se expressa nos terreiros - Vidal, Elisa Borri (2021)
Afro-Brazilian religions are, as cultural heritage, holders of civilizing values, memory, identity and ancestry, however, they never experienced freedom of worship and were (and still are) unceasingly persecuted, marginalized and silenced. This historical, social and political process is about racism, since, despite being religious minorities, AfroBrazilian religions are the strands most affected by hate speech and practices. The present research entitled “Let the gira girar: how religious racism is expressed in the terreiros” aims to problematize the socially constructed imagery of subalternization and demonization that fall sharply on the Traditional Communities of Terreiro (CTTro). It is also the desire of this study to be organizational tool in the fight against religious racism from the creation of the Gira Livre Movement (MOGILI). The qualitative and quantitative participatory methodology made possible, based on the contributions of the research subjects - followers of African religions - not only the construction of a network materialized in the mapping of the terreiros, but also provided a framework to analyze, under the Marxist perspective, how religious violence has impacted the daily lives of the people of axé and what strategies of struggle they have developed against religious racism. Religious racism is revealed as an expression of the genocide of the black people, insofar as it oppresses and violates their cultural heritage, however, the historical resistance of the traditional terreiro communities opposes the order of erasure and with much struggle and resistance they preserve in our society its diasporic ancestral knowledge, linguistics, aesthetics and rituals